2018
DOI: 10.1093/mnras/sty807
|View full text |Cite
|
Sign up to set email alerts
|

Study of central light concentration in nearby galaxies

Abstract: We propose a novel technique to estimate the masses of super massive black holes (SMBHs) residing at the centres of massive galaxies in the nearby Universe using simple photometry. Aperture photometry using SEXTRACTOR is employed to determine the central intensity ratio (CIR) at the optical centre of the galaxy image for a sample of 49 nearby galaxies with SMBH mass estimations. We find that the CIR of ellipticals and classical bulges is strongly correlated with SMBH masses whereas pseudo bulges and ongoing me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 49 publications
1
33
1
Order By: Relevance
“…This scenario is also supported in the present study as we find low values of central intensity ratios in strong bars. In the case of early-type systems, it was observed that low values of central intensity ratio suggest massive black holes in galactic centres (Aswathy & Ravikumar 2018). Thus, the CIR seems to possess the potential to play a crucial role in understanding the linked evolution of rings, bars and central AGNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scenario is also supported in the present study as we find low values of central intensity ratios in strong bars. In the case of early-type systems, it was observed that low values of central intensity ratio suggest massive black holes in galactic centres (Aswathy & Ravikumar 2018). Thus, the CIR seems to possess the potential to play a crucial role in understanding the linked evolution of rings, bars and central AGNs.…”
Section: Discussionmentioning
confidence: 99%
“…The CIR for early-type galaxies is reported to be anti-correlated with the mass of the supermassive black holes (SMBH, Aswathy & Ravikumar 2018). It is closely related to various structural and dynamical properties of host galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…The degree to which light or mass is centrally concentrated is an important diagnostic for galaxies. The importance is obvious when the many physical galaxy properties are considered that correlate with (different measures of) the galaxy light concentration, including total luminosity (Caon et al 1993;Graham et al 2001a), velocity dispersion (Graham et al 2001a), Mg/Fe abundance ratio (Vazdekis et al 2004), central supermassive black hole mass (Graham et al 2001b;Aswathy & Ravikumar 2018), cluster local density (Trujillo et al 2002b), and emission at radio and X-ray wavelengths (Pović et al 2009;Aswathy & Ravikumar 2018). This has inspired several teams to propose galaxy concentration as an important parameter in automated galaxy classification schemes (Doi et al 1993;Abraham et al 1994;Bershady et al 2000;Conselice 2003).…”
Section: Central Concentration Of the Sérsic Modelsmentioning
confidence: 99%
“…Contrary to other concentration indices (e.g. Trujillo et al 2001;Graham et al 2001a;Aswathy & Ravikumar 2018), it is based on the intrinsic 3D density distribution, rather than on the light distribution on the plane of the sky. In the past few years, the interest in the central light (or mass) concentration of galaxies has only increased, thanks to a number of scaling relations between the central 1 The use of this unit system has been strongly advocated by Heggie & Mathieu (1986), and as a result, these standard units have sometimes been called Heggie units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation